Abusive supervision and employee voice: The roles of positive reappraisal and employee cynicism - Sun, Wei; Dedahanov, Alisher Tohirovich; Fayzullaev, Abdulkhamid Komil ugli; Abdurazzakov, Odiljon Sobirovich (Frontiers in Psychology, 2022)
Purpose Despite the number of studies on abusive supervision and voice, there is still limited knowledge on why individuals refrain themselves from information sharing. Moreover, very little is known on when individuals become cynical and when they do not under abusive supervision. Hence, to address the existing gaps in the literature this study aims to investigate the moderating role of positive reappraisal on the link between abusive supervision and cynicism; the associations between cynicism and two forms of voice, promotive and prohibitive; and the mediating effect of cynicism on the relationship between abusive supervision and voice. Design/methodology/approach We conducted a survey among 685 highly skilled employees and their immediate supervisors in manufacturing companies. Among the 685 responses, we excluded 258 incomplete questionnaires and thus analyzed a total of 427 responses. Hierarchical regression analysis and structural equation modeling were utilized to assess the validity of the hypotheses. Findings The findings indicate that positive reappraisal moderates the link between abusive supervision and cynicism; furthermore, cynicism is negatively related to promotive voice and mediates the relationship between abusive supervision and promotive voice. Moreover, the results reveal that the association between cynicism and prohibitive voice is nonsignificant and that cynicism does not mediate the link between abusive supervision and prohibitive voice. Originality/value This study is the first to provide empirical evidence on the moderating role of positive reappraisal on the relationship between abusive supervision and cynicism, the association between cynicism and promotive voice and the mediating role of cynicism on the link between abusive supervision and promotive voice. Future research directions We recommend that future research consider other forms of voice, such as acquiescent and prosocial voice, in investigating the links between cynicism and employee voice.